Peer-Discussion in TOEFL Preparation Class - Nyak Mutia Ismail; Sri Wahyuni (IJEE (Indonesian Journal of English Education), 2017)
ABSTRACT The aim of this study was to see whether the technique of peer-discussion during the TOEFL preparation class benefits the students in increasing their score in Section Two of TOEFL Test,  Structure and Written Expression. According to Porter et al. (2001), during the process of students’ interaction with their peer(s), students have more open chances to ask conceptual questions; and as their peer(s) respond, they can understand more correctly and individually the questions. This study adopted quasi-experimental design involving  one class consisting of 24 second semester college students at Economics Faculty, Syiah Kuala University, Aceh, Indonesia. The result showed that the technique posed positive result on the students’ score in Section Two of TOEFL. The findings revealed that the Ha is accepted for the tvalue is 0.37 (df 22, α=0.05, -0.404 ≤ t ≥ 0.404 ). Also, it is significant for the sigvalue is 0.9 (sigvalue ≥ α=0.05). Hopefully, the result can contribute to the  theoretical gap in the TOEFL domain since there have not been many experimental studies about this technique used in TOEFL class. The technique indeed helps the students in overcoming the problems that they face in the Section Two of TOEFL. Besides, it can also boost their motivation in preparing for the TOEFL test.   ABSTRAK Tujuan dari studi ini adalah untuk melihat apakah diskusi dengan teman selama kelas persiapan TOEFL dapat memberi manfaat kepada siswa dalam meningkatkan skor mereka di bagian kedua tes TOEFL, yakni Structure and Written Expression. Seperti dikatakan oleh Porter et al. (2001) bahwa selama proses interaksi dengan teman, siswa mempunyai lebih banyak kesempatan untuk menanyakan pertanyaan konseptual; dan diwaktu mereka merespon, mereka mampu untuk mengerti dengan lebih baik dan secara individu pertanyaan tersebut. Studi ini menggunakan desain quasi-experimental yang melibatkan satu kelas yang terdiri dari 24 siswa dari semester 2 di Fakultas Ekonomi, Universitas Syiah Kuala University, Aceh, Indonesia. Hasil penelitian ini menunjukkan bahwa teknik ini mempunyai hasil positif terhadap skor siswa dalam bagian kedua tes TOEFL. Hasil yang didapat menerima Ha dengan nilai t 0.37 (df 22, α=0.05, -0.404 ≤ t ≥ 0.404 ). Dan hasil ini juga signifikan dengan nilai signifikansi 0.9 (sigvalue ≥ α=0.05).  Diharapkan hasil dari studi ini dapat memberi kontribusi kepada kajian teoritis dalam karena masih belum banyak studi eksperiment tentang ini dalam pengajaran TOEFL. Teknik ini mampu membantu siswa dalam menghadapi masalah dalam TOEFL di bagian kedua. Di samping itu, teknik ini juga mampu meningkatkan motivasi siswa di dalam menghadapi tes TOEFL.   How to Cite: Ismail, N. M. Wahyuni, S. (2017). Peer-Discussion in TOEFL Preparation Class. IJEE (Indonesian Journal of English Education), 4(1), 63-70 doi:10.15408/ijee.v4i1.4837.DOI: http://dx.doi.org/10.15408/ijee. v4i1.4837